Modeling and experiments of a soft robotic gripper in amphibious environments. (29th May 2017) - Hao, Yufei; Wang, Tianmiao; Ren, Ziyu; Gong, Zheyuan; Wang, Hui; Yang, Xingbang; Guan, Shaoya; Wen, Li
This article presented the optimization parameter of a bidirectional soft actuator and evaluated the properties of the actuator. The systematic simulation was conducted to investigate the effect of the top wedged angle (the angle for the wedged shape of the actuator structure) of the chamber on the bending extent of the actuator when it is deflated. We also investigated the width of the actuator and the material combinations of the two layers with the relation to the deformation performance. A mathematical model was also built to reveal the deformation of the actuator as a function of the geometrical parameters of the inner chambers and the material properties. We quantitatively measured the bending radius and the actuation time of the actuator both in air and under water. Digital particle image velocimetry experiments were conducted under water to observe the flow patterns around the actuator. We found that the top wedged angle has a significant effect on the outward bending of the actuator when it is deflated, and 15° was found to be optimal for bending into a larger gripping space. The result shows that the actuator can deform much easier with a bigger width. Utilizing a soft gripper that was built by mounting four actuators to a three-dimensional-printed rigid support, we found that the prototype can grip objects of different sizes, shapes, and material stiffness in amphibious environments.